2012
DOI: 10.2174/1874306401206010160
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Fibroproliferative Healing in Fibrosing Idiopathic Interstitial Pneumonias

Abstract: Aims:The main feature of fibrosing idiopathic interstitial pneumonias (fIIPs) is the fibroproliferative potential of underlying pathogenetic process. We hypothesize that the concentration of potential markers of fibroproliferative healing, PAR-2, TGF-β1, TNF-α and IL-4Rα in bronchoalveolar lavage fluid (BALF) differ in patients with fIIPs compared to controls (C).Patients and Methods:10 patients with fIIPs and 9 controls (C) were included to the study.Concentrations of CD124 (IL4Rα), PAR-2, TGF-β1 and TNF-α in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…The positive correlation between IS and IL-4Rα supports our previous results, where we measured significantly higher concentrations of IL4-Rα in the BALF of patients with fIIP compared to controls [18]. IL-4Rα has been recognized as a key cytokine in the process of progressive fibrosis.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The positive correlation between IS and IL-4Rα supports our previous results, where we measured significantly higher concentrations of IL4-Rα in the BALF of patients with fIIP compared to controls [18]. IL-4Rα has been recognized as a key cytokine in the process of progressive fibrosis.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the concentrations of TNF-α in BALF were significantly lower in fIIP and CTD-ILD compared to HP. According to our previous [18,43] and present studies, we suggested that TNF-α levels are indicative of lung tissue inflammation, especially in the early phases of HP, rather than fibroproliferation. On the other hand, chronic stages of HP are characterized by more pronounced fibroproliferation rather than inflammation or granuloma formation, which is represented by an overexpression of IL-4Rα, as we previously described [44].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations